Influência do diâmetro do folículo dominante sobre as taxas de ovulação e gestação de vacas da raça Gir em anestro pós-parto submetidas a protocolo hormonal com progesterona associada a estradiol - Thiago Fernandes Amaral (2009)
This study was done to evaluate the influence of the dominant follicle diameter at beginning of progesterone and estradiol protocol, on ovulation and pregnancy rates of 100 postpartum anestrous Gyr cows. Cows were maintained on pasture and under twice daily suckling, average 66.1 24.5 days postpartum. Animals were allocated into four treatments with 25 animals each ones: T1 = diameter of dominant follicle less than 10 mm and not treated with hormonal protocol; T2 = diameter of dominant follicle less than 10 mm and treated with progesterone and estradiol protocol; T3 = diameter of dominant follicle greater than or equal to 10 mm and not treated with hormonal protocol; and T4 = diameter of dominant follicle greater than or equal to 10 mm and treated with progesterone and estradiol protocol. Ultrasonographic examinations were made on the ovaries to monitoring the follicular diameter on days of progesterone device insertion (day 0), to detect corpus luteum on days 8 and 21 after ovulation, and at day 30 of pregnancy. Estrus detection was performed twice daily and artificial inseminations after 12 hours. Blood samples were obtained on same days of ultrasonographic examinations for determination of progesterone concentration. Standing estrus was detected in 4% of the cows of T1 and T3, and in 100% of animals in T2 and T4. Spontaneously ovulation was detected in 16% and 28% of the cows of nontreated grous (T1 and T3, respectively), while 60% (T2) and 88% (T4) of animals ovulated after progesterone and estradiol protocol. Pregnancy rates after 30 days of artificial inseminations were 52% of cows from T4, and 0%, 20% and 16% of females of T1, T2 and T3, respectively. The area (cm2) and volume (cm3) of the corpus luteum did not differ between pregnant cows from T2 and T4, but the volume increased linearly as a function of days after induction of ovulation